Reforming the labour market: an assessment of the UK policies of the Thatcher era - Gregory, M (Blackwell Publishers Ltd., 1998)
Under Thatcher the United Kingdom introduced a major program of labour market deregulation, claimed to have made the United Kingdom one of the least regulated labour markets in the OECD. This paper reviews the measures implemented and assesses their impact. Trade union membership declined steeply, and collective bargaining was curtailed even more sharply. The impact of the legislation curbing unions can be exaggerated, given that it coincided with wider developments. At the microeconomic level there is some evidence that the decline of unions contributed to productivity gains, but no clear evidence on employment, investment, profitability or wage premia. UK macroeconomic performance improved, but not dramatically. The most marked features of the more flexible labour markets are the growth of part-time and temporary work, while job insecurity has become a common perception. The most striking development is the growth in earnings inequality, in part reflecting the weakening of collective bargaining. The evolution and consequences of inequality will be a major criterion in assessing the moves to labour market flexibility.